2013
DOI: 10.1111/hae.12296
|View full text |Cite
|
Sign up to set email alerts
|

Comparative field study evaluating the activity of recombinant factor VIII Fc fusion protein in plasma samples at clinical haemostasis laboratories

Abstract: Discrepancies exist for some of the modified coagulation factors when assayed with different one-stage clotting and chromogenic substrate assay reagents. The aim of this study was to evaluate the performance of a recombinant factor VIII Fc fusion protein (rFVIIIFc), currently in clinical development for the treatment of severe haemophilia A, in a variety of one-stage clotting and chromogenic substrate assays in clinical haemostasis laboratories. Haemophilic plasma samples spiked with rFVIIIFc or Advate® at 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
137
4
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(160 citation statements)
references
References 22 publications
(53 reference statements)
16
137
4
3
Order By: Relevance
“…Both studies identified higher chromogenic assay results compared to one stage results when FVIII was in the 60-90 IU/dl range (by 12-19%) but either no difference ( 22) or lower (17) chromogenic assay results for samples containing 3-5 IU/dl FVIII.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Both studies identified higher chromogenic assay results compared to one stage results when FVIII was in the 60-90 IU/dl range (by 12-19%) but either no difference ( 22) or lower (17) chromogenic assay results for samples containing 3-5 IU/dl FVIII.…”
Section: Discussionmentioning
confidence: 94%
“…Samples containing Advate spiked into severe haemophilic plasma have been included in multi -centre studies of FVIII assays in relation to newer concentrates (17,22). Both studies identified higher chromogenic assay results compared to one stage results when FVIII was in the 60-90 IU/dl range (by 12-19%) but either no difference ( 22) or lower (17) chromogenic assay results for samples containing 3-5 IU/dl FVIII.…”
Section: Discussionmentioning
confidence: 99%
“…Based on reports indicating that FVIII activity of full-length rFVIII products is approximately 20% lower with the one-stage assay vs. the chromogenic assay [7,8], the LEOPOLD program included an intraindividual comparison of the clinical efficacy of prophylaxis using potency labelling based on the chromogenic substrate assay per European Pharmacopoeia (CS/EP) or adjusted by a predefined factor to mimic results obtained with the one-stage assay (CS/ADJ). Results of the LEOPOLD II trial, which demonstrated the superiority of two-and three times-weekly prophylaxis dosing of BAY 81-8973 over on-demand treatment, have been published [9].…”
Section: Introductionmentioning
confidence: 99%
“…For measurement of ADVATE as a commercially available product with more than 14 years of experience in clinical use, variability seemed to be in the expected range and recent studies demonstrated no relevant discrepancies when measuring this product with different assay methods and in different laboratories [29,30]. Thus, ADVATE provided a point of comparison to determine the extent of variability between methods.…”
mentioning
confidence: 99%